2011
DOI: 10.1126/science.1198878
|View full text |Cite
|
Sign up to set email alerts
|

Classic Selective Sweeps Were Rare in Recent Human Evolution

Abstract: Efforts to identify the genetic basis of human adaptations from polymorphism data have sought footprints of “classic selective sweeps”. Yet it remains unknown whether this form of natural selection was common in our evolution. We examined the evidence for classic sweeps in resequencing data from 179 human genomes. As expected under a recurrent sweep model, diversity levels decrease near exons and conserved non-coding regions. In contrast to expectation, however, the trough in diversity around human-specific am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
485
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(530 citation statements)
references
References 34 publications
40
485
2
3
Order By: Relevance
“…For example, if a human population experienced 1200 recent sweeps fairly evenly spaced across the genome (the equivalent of one recent sweep in 5% of genes), every site in the genome would be within a c/s distance of 0.5 (assuming s = 0.05) from the nearest sweep (i.e., f = 1.0). This is likely an unrealistic scenario in human populations, where positive selection is perhaps less common (Hernandez et al 2011). However, some have argued that selection may be pervasive in the human genome as well (Boyko et al 2008;Enard et al 2014), and certainly humans show many adaptations to local environments (e.g., Li et al 2007;Perry et al 2007;Tishkoff et al 2007;Barreiro et al 2008;Bryk et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if a human population experienced 1200 recent sweeps fairly evenly spaced across the genome (the equivalent of one recent sweep in 5% of genes), every site in the genome would be within a c/s distance of 0.5 (assuming s = 0.05) from the nearest sweep (i.e., f = 1.0). This is likely an unrealistic scenario in human populations, where positive selection is perhaps less common (Hernandez et al 2011). However, some have argued that selection may be pervasive in the human genome as well (Boyko et al 2008;Enard et al 2014), and certainly humans show many adaptations to local environments (e.g., Li et al 2007;Perry et al 2007;Tishkoff et al 2007;Barreiro et al 2008;Bryk et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to study background selection and understand how its interplay with other evolutionary forces such as demographic changes can shape genomewide patterns of diversity. The importance of this has been highlighted by several recent examinations of DNA sequence polymorphisms in humans (McVicker et al, 2009;Hernandez et al, 2011;Lohmueller et al, 2011), Caenorhabditis (Cutter and Choi, 2010) and rice (Flowers et al, 2012) whereby broad-scale patterns of variability have been found to be compatible with predictions of a background selection model. Furthermore, there is evidence that background selection may explain the observation that the ratio of silent DNA sequence diversity for X-linked loci to that for autosomal loci is approximately one in East African populations of Drosophila melanogaster, instead of the expected value of three quarters (Charlesworth, 2012b).…”
Section: Introductionmentioning
confidence: 91%
“…A recent analysis of the 1000 Genomes Project data also suggests the plausibility that hard sweeps are rare across humans [51]. Under models of hard sweeps, one expects a reduction in genetic diversity around locations where amino acid substitutions have taken place.…”
Section: Insights From Recent Genomic Studies Of Human Adaptive Evolumentioning
confidence: 99%
“…Under models of hard sweeps, one expects a reduction in genetic diversity around locations where amino acid substitutions have taken place. In the analysis of the 1000 Genomes pilot data, Hernandez et al [51] found the trough in diversity around non-synonymous sites was not lower than that around synonymous substitutions (which serve as a form of internal control for other factors than recent selection affecting diversity). The results suggest that hard sweeps must be uncommon relative to soft sweeps, or if they are common, the selective pressures associated with the hard sweeps must be quite weak.…”
Section: Insights From Recent Genomic Studies Of Human Adaptive Evolumentioning
confidence: 99%